Pemberdayaan Lanjut Usia dalam Menunjang Successful Aging Melalui Pos Sehat Al-Falah Dompet Dhuafa di Kecamatan Cinere - Dhiya Sausan Rizky Angreni; Almisar Hamid (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The elderly period carries a negative perception because it is considered one of the vulnerable groups in society. They often experience changes in physical health, reduced social support, and the possibility of decreased quality of life. In this case, empowerment of the elderly is important to improve the quality of life and achieve successful aging, as is the empowerment carried out for the elderly at the Al-Falah Health Post Dompet Dhuafa. This study aims to determine what empowerment model is carried out at the Al-Falah Health Post and what programs are carried out in achieving successful aging for the elderly at the Al-Falah Health Post as well as the obstacles and what efforts are made to overcome these obstacles. This study uses a descriptive qualitative research method. Data collection was carried out by interviews, observations, and documentation. And the determination of informants used purposive sampling. The results of this study show a picture of empowerment at the AL-Falah Health Post involving various training for elderly cadres, the achievement of successful aging in the elderly at the Al-Falah Health Post in the forms of achievements include: a) minimizing and low risk of disease, the elderly have awareness and commitment to maintain their health, b) physical and cognitive function that is still maximal allows the elderly to continue learning, maintain physical and mental health, and increase their independence in everyday life, c) social relationships in life at the Al-Falah Health Post create an environment that supports active and beneficial social relationships.